Factors influencing long-term care facility performance during the COVID-19 pandemic: a scoping review - Tchouaket, Eric N.; Kruglova, Katya; Létourneau, Josiane; Bélanger, Emilie; Robins, Stephanie; Jubinville, Maripier; El-Mousawi, Fatima; Shen, Shiyang; Beogo, Idrissa; Sia, Drissa (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background The COVID-19 pandemic wreaked havoc on long-term care facilities (LTCFs). Some LTCFs performed better than others at slowing COVID-19 transmission. Emerging literature has mostly described infection prevention and control strategies implemented by LTCFs during the pandemic. However, there is a need for a comprehensive review of factors that influenced the performance of LTCFs in containing COVID-19 spread to inform public health policy. Objective To build on the existing literature, we conducted a scoping review of factors that influenced LTCF performance during the COVID-19 pandemic using a multidimensional conceptual framework of performance. Methods We followed the Joanna Briggs Institute’s methodology for scoping reviews. We queried CINAHL, MEDLINE (Ovid), CAIRN, Science Direct, Scopus, and Web of Science for peer-reviewed literature in English or French published between January 1st, 2020 and December 31st, 2021. Retrieved records were screened for context (COVID-19 pandemic), population (LTCFs), interest (internal and external factors that influenced LTCF performance), and outcomes (dimensions of performance: equity, accessibility, reactivity, safety, continuity, efficacy, viability, efficiency). Descriptive characteristics of included articles were summarized. Dimensions of performance as well as internal (e.g., facility characteristics) and external (e.g., visitors) factors identified to have influenced LTCF performance were presented. Results We retained 140 articles of which 68% were classified as research articles, 47% originated in North America, and most covered a period between March and July 2020. The most frequent dimensions of performance were “efficacy” (75.7%) and “safety” (75.7%). The most common internal factors were “organizational context” (72.9%) and “human resources” (62.1%), and the most common external factors were “visitors” (27.1%) and “public health guidelines” (25.7%). Conclusions Our review contributes to a global interest in understanding the impact of the COVID-19 pandemic on vulnerable populations residing and working in LTCFs. Though a myriad of factors were reported, a lack of randomized controlled trials makes it impossible to establish causality between the identified factors and LTCF performance. The use of a multidimensional framework can be recommended to evaluate healthcare system performance not merely in terms of efficacy and safety, but alongside other critical dimensions such as efficiency and equity. Trial registration Research Registry ID: researchregistry7026